Children malnutrition and food insecurity as expression of socio-economic conditions of families from Villaguay, Argentina (2010-2012). A biocultural approach - Bergel Sanchís, María Laura (2016)
Objective: To inquire: a) if there are differences in living conditions estimated through socio-economic variables among families with 3 to 6 years old children, living in urban, peri-urban and rural areas of Villaguay department, Entre Ríos, Argentina; and b) in case there is any, whether these differences are expressed in child nutritional status and in the perception of households food insecurity (PHFI) (regarding access). Population and Methods. The study was transverse and included 303 children aged 3 to 6 years old. For the anthropometric study, we considered body weight and height, along with The Third National Health and Nutrition Examination Survey (Frisancho, 2008) reference to determine nutritional status indicators. Socioeconomic information was inquired through a semistructured survey, while the PHFI was obtained from the survey proposed by the Academy for Educational Development (AED), both filled by parents of children measured anthropometrically. Results and Conclusion. In general, it was observed that the studied populations showed socio-economic differences in relation to parental education level and employment, critical overcrowding, and health insurance, among others; these differences might be expressed in the differential distribution of children malnutrition and in the perception of the limitations that parents said to have to a good nutrition both in terms of quantity and quality.